2014
DOI: 10.1002/2013jd021003
|View full text |Cite
|
Sign up to set email alerts
|

Mixing state and hygroscopicity of dust and haze particles before leaving Asian continent

Abstract: Pollutants during haze and Asian dust storms are transported out of the Asian continent, affecting the regional climate and the hydrological and biogeochemical cycles. Understanding the physicochemical properties of aerosol particles is essential to quantify their impacts. In order to determine physicochemical properties of aerosols before leaving the Asian continent, we carried out a field campaign from 14 April to 2 May 2011 at a background site in the path of Asian dust and haze outflows. We measured concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 79 publications
7
67
1
Order By: Relevance
“…A number of studies in China reported that dust particles significantly enhanced the formation of sulfate and nitrate when dust plumes advected over urban areas (Li and Shao, 2009;Li et al, 2014;Nie et al, 2012;Qi et al, 2006;Sheng et al, 2003;Wang et al, 2013;Zhao et al, 2011Zhao et al, , 2007, which is very different from the conclusions of this study. We carefully examined the available meteorological records for the dust episodes in those studies.…”
Section: Intercomparisons and Implicationscontrasting
confidence: 89%
“…A number of studies in China reported that dust particles significantly enhanced the formation of sulfate and nitrate when dust plumes advected over urban areas (Li and Shao, 2009;Li et al, 2014;Nie et al, 2012;Qi et al, 2006;Sheng et al, 2003;Wang et al, 2013;Zhao et al, 2011Zhao et al, , 2007, which is very different from the conclusions of this study. We carefully examined the available meteorological records for the dust episodes in those studies.…”
Section: Intercomparisons and Implicationscontrasting
confidence: 89%
“…Z. . The phenomenon was also observed in Shanghai, a megacity a few thousands of kilometers from dust source zones in China, and more downwind sites (Kang et al, 2013;Li et al, 2014;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 69%
“…In an extreme case, Asian dust was found to be transported more than one full circuit around the globe in approximately 13 days (Uno et al, 2009). During long-range transport, dust particles may mix with anthropogenic air pollutants and consequently undergo complicated chemical reactions Li et al, 2014;Ma et al, 2012;Q. Z. Wang et al, 2011Q.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mineral dust particles normally display irregular shapes and fly ash particles are spherical, although they both have similar elemental composition, such as Si and Al. A detailed particle classification scheme is described in our previous studies (Li et al, 2014b. The nanometer-sized metal particles which have been frequently detected in ambient aerosols in East China (W. Li et al, 2013a, b) were absent in the Qinghai-Tibet plateau.…”
Section: Major Fine Aerosol Particles and Mixing Statesmentioning
confidence: 99%